Analysis the Impact of Halal Certification and Marketing Mix On the Development of Small and Medium Enterprises Smess in Kebumen - Sofy, Yuyun Amalia; Lestari, Niken; Aliefah, Aniesatun Nurul (UM Purwokerto Press, 2025)
This study aims to determine the effect of halal certification and marketing mix consisting of product, price, promotion, place (4P) on increasing sales of MSEs in Kebumen Regency. The object of this study is MSEs in the food and beverage sector that has been halal certified through the self-declaration scheme. The sampling technique used a non-probability sampling technique with a purposive sampling method and a sample of 83 respondents was taken. The results of the study showed that the value of the halal certification variable was 0.004 <0.05, meaning that the variable had a significant effect on the sales increase variable. The significance value of the product quality variable was 0.000 <0.05, meaning that the variable had a significant effect on the sales increase variable. The significance value of the price variable was 0.001 <0.05, meaning that the variable had a significant effect on the sales increase variable. The significance value of the promotion variable was 0.418> 0.05, meaning that the variable did not have a significant effect on the sales increase variable. The significance value of the location variable was 0.000 <0.05, meaning that the variable had a significant effect on the sales increase variable. Overall, halal certification, product quality, price, promotion, and location have a significant effect on increasing sales with a significance of 0.000 <0.05 and an Adjusted R-Square of 66.8%, which means that they can contribute to increasing sales and the remaining 33.2% is influenced by other factors not discussed in this study.